A crítica de Hannah Arendt à universalidade vazia dos direitos humanos: o caso do refugo da terra - Pereira, Ana Paula Silva (2014)
In The Origins of Totalitarianism, one of the issues raised by Hannah Arendt, concerns the supposed universality of human rights and how they become brittle in the face of exception situations in which a large group of people lost their most basic rights. The question posed by the author is referring to the dichotomy x human rights of citizens rights. The great mass of people who lost their citizenship or were forced to seek refuge in another country, without being thereby assimilated into this new territory and unable to return to their home territory, feeling constantly threatened by not more having a place where you feel at home in the world, therefore, found themselves thrown in concentration camps or in internment camps had become a constant of the twentieth century, when two world wars put millions of people in the situation of refugees and stateless . These stateless persons and refugees were not only a constant in the last century, today, millions of people continue to flee their country to seek refuge elsewhere. Even with the many advances in legislation of international law with regard to the fragile situation in which they are stateless and refugees, it would still be unwise to assert the universality of human rights. And that is what Hannah Arendt's critique of human rights continues today: it consists in saying that the so-called "inalienable rights" were never effective in protecting or stateless persons or refugees, and all other "waste" land . Contemporary authors such as Giorgio Agamben faced with the thought of Arendt, upgrading these themes. The homo sacer, legal figure of Roman law, is brought by Agamben to explain the condition of these people who live outside of society, and are excluded from the right. Arendt's critique of universal human rights aspect is updated by Agamben deepens that resuming old concepts such as homo sacer, a bunch of field, which are fundamental to understanding the numerous conflicts that happen in the world today.